THE NATIONAL EXPRESSIONS OF BIRDS AND ANIMALS’ IMAGES IN THE WORKS OF ALISHER NAVOI (Scientific journal of the Fergana State University, 2023)
Various types of poetonyms can be observed in Alisher Navoi’s creative activity. The article discusses zoopoetonyms and ornithomythopoetonyms formed on the basis of folk artistic thoughts. The ideas and motifs interpreted artistically via mythological images such as birds and animals are depicted through analysis.